Usulan Seleksi Karyawan Menggunakan Metode Fuzzy Technique For Order Preference By Similarity To Ideal Solution (Topsis) Di Cafe X - ARIAN, M DHAFA PUTRA (e-Proceeding FTI, 2024)
Cafe X is a company engaged in the coffee industry which was founded in 2015 and is located in Bandar Lampung. Companies must always try to obtain and place qualified employees in each position so that the implementation of work is more empowered and in accordance with the needs of the company. The problem that occurred at Cafe X was because the selection of the head of the warehouse did not carry out the employee selection process based on the criteria needed by the company but only based on a subjective assessment of the interview results. Therefore, companies need criteria that match the company’s needs to minimize the criteria needed by the company but only based on a subjective assessment of the interview results. Therefore, companies need criteria that match the company’s needs to minimize the high level of subjectivity in order to determine the selection of the best employees. This problem can be solved using a Multi-Attribute Decision Making (MADM) decision-making model, namely Fuzzy Technique For Order Preference By To Similarity Ideal Solution (TOPSIS). The TOPSIS method is used to rank and provide a weighted assessment of the selected criteria to determine the best solution. This method assumes that each criterion in the study will be maximized or minimized so that positive ideal solutions and negative ideal solutions are obtained from each criterion. So that from the 4 employees who were selected, it was found that the one who ranked first was Abizar Aris with a preference value of 0.615. Abstrak Cafe X adalah perusahaan yang bergerak dibidang industri kopi yang berdiri sejak tahun 2015 yang terletak di Bandar Lampung. Perusahaan harus selalu berusaha untuk memperoleh dan menempatkan karyawan yang qualified pada setiap jabatannya supaya pelaksanaan pekerjaan lebih berdaya serta sesuai dengan kebutuhan perusahaan. Permasalahan yang terjadi di Cafe X dikarenakan pemilihan kepala gudang tidak melakukan proses seleksi karyawan berdasarkan kriteria yang dibutuhkan perusahaan, namun hanya berdasarkan penilaian secara subjektif dari hasil wawancara saja. Oleh karena itu perusahaan membutuhkan kriteria-kriteria yang sesuai kebutuhan perusahaan untuk meminimasi tingkat subjektivitas yang tinggi agar dapat menentukan pemilihan karyawan terbaik. Permasalahan tersebut dapat diselesaikan menggunakan sebuah model pengambilan keputusan Multi Attribute Decision Making (MADM) yaitu Fuzzy Technique For Order Preference By To Similarity Ideal Solutiun (TOPSIS). Metode TOPSIS digunakan untuk merangking dan memberikan penilaian pembobotan dari kriteria yang terpilih untuk menentukan solusi terbaik. Metode ini mengasumsikan setiap kriteria dalam penelitian akan dimaksimalkan atau diminimalkan sehingga mendapat solusi ideal positif dan solusi ideal negatif dari setiap kriteria. Sehingga dari 4 karyawan yang diseleksi didapatkan bahwa yang menempati rangking pertama adalah Abizar Aris dengan nilai preferensi 0,615.